2017
DOI: 10.4103/1450-1147.215492
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative metabolic volumetric product on 18Fluorine-2fluoro-2-deoxy-D-glucose-positron emission tomography/computed tomography in assessing treatment response to disease-modifying antirheumatic drugs in rheumatoid arthritis: Multiparametric analysis integrating American college of Rheumatology/European League against Rheumatism criteria

Abstract: The purpose of this study was to assess the role of fluoro-2-deoxy-D-glucose-positron emission tomography/computed tomography (FDG-PET/CT) in the evaluation of treatment response evaluation to disease-modifying antirheumatic drug (DMARD) therapy in patients of rheumatoid arthritis (RA). A total of ten patients with proven diagnosis of RA as per the 2010 American College of Rheumatology/European League against Rheumatism (EULAR) criteria were prospectively evaluated. All patients underwent clinical and biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Some other studies, however, used ROIs manually drawn by nuclear physicians and radiologists [ 8 , 11 , 37 , 38 ] or created through the use of different types of software and dedicated workstations [ 9 , 22 , 39 , 40 ]. Many studies also used SUVmax [ 12 , 40 , 41 ] instead of SUVmean, which could have varied results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies, however, used ROIs manually drawn by nuclear physicians and radiologists [ 8 , 11 , 37 , 38 ] or created through the use of different types of software and dedicated workstations [ 9 , 22 , 39 , 40 ]. Many studies also used SUVmax [ 12 , 40 , 41 ] instead of SUVmean, which could have varied results.…”
Section: Discussionmentioning
confidence: 99%
“…While an abundance of previous research has focused on imaging with MRI, considering it the “gold standard”, recent studies have been analyzing the usefulness of PET in combination with CT. In fact, when compared to MRI, FDG PET showed promising results in many of the RA studies in both the more commonly studied small joints and the less often studied large joints [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The aim of this study is to explore the feasibility of calculating the FDG and NaF mean SUV (SUVmean) in the knee joint, hip joint, and sacroiliac (SI) joint of RA patients and to determine the association of these values with clinical characteristics of patients with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicated that there was a significant correlation between the visual assessment of 18 F-FDG uptake, i.e., visual uptake score and clinical evaluation of disease activity. [ 7 ] Furthermore, PET findings have been correlated with magnetic resonance imaging (MRI) and ultrasonography (US) assessments of the pannus in patients with RA as well as with the classical serum parameter of inflammation, CRP and MMP-3.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, there has been growth in PET utilization in systemic infections and inflammation for diagnosis, assessment of disease activity, and therapy monitoring [ 45 , 46 ]. FDG PET/CT can be used for diagnosis and follow-up in multiple inflammatory conditions including rheumatoid arthritis (RA) [ 47 ], polymyalgia rheumatica [ 48 ], IgG4-relate disease, large vessel vasculitis [ 49 ], and granulomatosis with polyangiitis, adult-onset Still disease [ 50 , 51 ], spondyloarthritis, chronic osteomyelitis, and multicentric reticulohistiocytosis [ 52 ]. Increased FDG uptake in the tracheobronchial tree is a reliable sign of cartilage involvement in relapsing polychondritis [ 53 ].…”
Section: Infection/inflammation Evaluationmentioning
confidence: 99%